Legal Review of Land Lease Agreement by Village Head Exceeding His Term of Office - Enno Sellya Agustina (Yayasan Tranformasi Aksara Digital, 2024)
Problems related to the lease of land between the village head and private parties that exceed the term of office raise legal issues regarding the validity of the agreement. This research aims to analyze the validity of the lease agreement based on applicable law. The method used is normative juridical with a statutory and case approach. The research findings show that the validity of the agreement is regulated in Permendagri Number 1 of 2016 concerning Village Asset Management, which limits the lease period to a maximum of three years. If the lease period exceeds the term of office of the village head, the agreement is null and void. In addition, this study found that violations of these provisions not only have the potential to cause losses to the parties involved, but can also disrupt the governance of village assets that should be utilized for the benefit of the wider community. The existence of strict regulations is necessary to ensure that the management of ganjaran land is carried out in accordance with the principles of transparency, accountability, and legal certainty. The legal implications of agreements that violate the rules also include the responsibility of the village head for the losses incurred, both materially and immaterially. This research is expected to contribute to the formulation of more effective policies in managing village assets in order to provide optimal benefits for the welfare of the community.